한국 청소년의 스마트폰 사용과 구강질환 증상과의 관련성 - 김선숙; Sun-sook Kim; 윤혜정; Hye-jeong Youn (Han'guk Ch'iwisaeng Hakhoe chi, 2023)
Objectives: This study aimed to determine the relationship between hours of smartphone use and oral disease symptoms in Korean adolescents. Methods: In this study, data from the 2022 Youth Health Behavior Online Survey were used. The final analysis was conducted on students who responded that they have used a smartphone (N=50,375). Chi-squared test and multivariate logistic regression analysis were used to analyze the relationship between oral disease symptoms and smartphone use time (p< 0.05). Results: Consequent to examining the effect of smartphone use on oral disease symptoms, it was found that oral symptoms, such as pain during chewing and tingling throbbing, increased as smartphones were used for >4 h (p< 0.05). Additionally, oral symptoms, such as gingivalgia bleeding and bad breath, appeared to increase as smartphones were used for >6 h (p<0.05). However, using smartphones for <0-2 h or 2-4 h had no effect on oral disease symptoms. Conclusions: In adolescents, oral disease symptoms increased significantly with increasing hours of smartphone use. Therefore, adolescents should be guided so that they use smartphones for < 2 h or >4 h. Moreover, guidance on forming the habit of tooth brushing after eating food should be provided to prevent oral disease symptoms.